PERAN GURU DALAM MENINGKATKAN PERKEMBANGAN EMPATI ANAK USIA 4-5 DI TK SANTA MARIA PONTIANAK - Ifir, Yuspina; Ali, Muhammad; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the role of teachers in improving empathy development of children aged 4-5 years at the TKK Santa Maria Pontianak Kota because of the importance of empathy from an early age to be able to understand the situation of others well. The formulation of the problem in this study was; how is the role of the teacher as a facilitator, the teacher as a model and the teacher as a motivator in improving the development of children's empathy. The research method used was descriptive with a form of qualitative research. There are four data analysis used in this study, namely: domain analysis, taxonomic analysis, compound analysis and cultural theme analysis. The data source of this research was the result of three teachers teaching class A in the TKK Santa Maria Pontianak Kota. The results showed that the teacher's role in enhancing the development of children's empathy with satisfactory levels was that the teacher has tried the material and time, the teacher gave a good example and the teacher gave a good enthusiasm so that the child's empathy ability could be said to develop according to expectations. Based on the results of the study it is suggested that teachers in Class A TKK Santa Maria Pontianak Kota to maintain and enhance their role so that children are motivated and brave to develop empathy skills even better.Â Keywords: Childrenâ€™s empathy, Improving the development, Teacherâ€™s role